2014
DOI: 10.1177/0269881114545663
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of alcohol- and non-alcohol-related stimuli processing in binge drinkers: A follow-up study

Abstract: Background: The continuation of binge drinking is associated with the development of neurocognitive brain abnormalities similar to those observed in patients with alcohol dependence. Alcohol cue reactivity constitutes a risk marker for alcohol dependence. Through event-related potentials (ERPs), we aimed to examine its potential presence as well as its evolution over time in binge drinkers in a one-year period. Methods: ERPs were recorded during a visual oddball task in which controls (n=15) and binge drinkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 99 publications
3
15
2
Order By: Relevance
“…This experimental design has led to important insights by showing a specific effect of the binge drinking pattern, a variation of the brain impairments according to the intensity of binge drinking, and a wide range of cerebral alterations (from early to later stages). Moreover, this amplitude reduction in binge drinkers was confirmed at early (P100) and later (P3b) stages of cognitive processing (Ehlers et al, 2007; Petit et al, 2014). The study by Ehlers et al (2007) used a facial discrimination task and highlighted a shorter latency for attentional processes related to novelty (P3a) and a reduced amplitude for decisional processes (P3b).…”
Section: Cerebral Modifications Associated With Binge Drinkingmentioning
confidence: 67%
See 1 more Smart Citation
“…This experimental design has led to important insights by showing a specific effect of the binge drinking pattern, a variation of the brain impairments according to the intensity of binge drinking, and a wide range of cerebral alterations (from early to later stages). Moreover, this amplitude reduction in binge drinkers was confirmed at early (P100) and later (P3b) stages of cognitive processing (Ehlers et al, 2007; Petit et al, 2014). The study by Ehlers et al (2007) used a facial discrimination task and highlighted a shorter latency for attentional processes related to novelty (P3a) and a reduced amplitude for decisional processes (P3b).…”
Section: Cerebral Modifications Associated With Binge Drinkingmentioning
confidence: 67%
“…The study by Ehlers et al (2007) used a facial discrimination task and highlighted a shorter latency for attentional processes related to novelty (P3a) and a reduced amplitude for decisional processes (P3b). The study of Petit and colleagues (2014) confirmed this amplitude reduction for early and later electrophysiological components after 1 year of binge drinking by using a visual oddball task. Compared with control participants, binge drinkers also demonstrated a reduced late positive component under a high working memory load (Crego et al, 2010).…”
Section: Cerebral Modifications Associated With Binge Drinkingmentioning
confidence: 78%
“…Although comparatively much less studied, electrophysiological measures of brain activity also appear to be sensitive to the BD pattern (López-Caneda et al, 2014a ; Petit et al, 2014b ). As such, anomalous brain responses have been documented in BD youths during cognitive tasks using event-related potentials (ERPs) and event-related oscillations (EROs; Crego et al, 2009 ; Maurage et al, 2012 ; Smith and Mattick, 2013 ; Petit et al, 2014a ; Watson et al, 2014 ; López-Caneda et al, 2017 ). Despite its well documented potential for detecting neurofunctional anomalies in chronic alcoholics, brain activity during task-free resting states has been virtually unaddressed in the BD population.…”
Section: Introductionmentioning
confidence: 99%
“…In line with earlier studies [e.g., Refs. (42, 59, 64, 65)], three variables (self-reported by participants through the use of a timeline follow-back method questionnaire assessing alcohol–drug consumption characteristics) were used to determine control and heavy alcohol user groups: the mean number of drinking occasions per week (DOW: “how many times do you typically consume alcohol in a week?”), the mean number of alcohol doses per drinking occasion (ADO: “how many drinks do you generally consume during one drinking occasion?”), and the mean number of alcohol doses per week (ADW: “how many drinks do you generally consume in a week?”; one dose corresponding to 10 g of pure ethanol). According to the definition of binge drinking used in European countries, participants who drank six or more standard alcoholic drinks (10 g of alcohol) on the same occasion at a rate of at least two drinks per hour and at most two or three times per week were classified as hazardous drinkers.…”
Section: Methodsmentioning
confidence: 99%